Formes, facteurs et importance de la vulnérabilité hydrique dans une métropole européenne - Xavier May; Pauline Bacquaert; Jean-Michel Decroly; Léa de Guiran; Chloé Deligne; Pierre Lannoy; Valentina Marziali (EchoGéo)
This article deals with the difficulties of access to water for hygiene (for washing, accessing a toilet or washing clothes) encountered by people living in Brussels. We highlight the notion of water vulnerability, which takes into account the difficulties of access to water due to its cost, housing characteristics (leakage, absence of basic sanitary equipment, etc.) or absence of housing. We show that at least 100,000 people, i.e. 8.2% of the Brussels population, are in water vulnerability because of the impoverishment of the Brussels population and lack of public sanitary infrastructures (in particular showers, fountains and public toilets).